Stability of Quantitative Traits through Analysis of Rice Diversity (Oryza Sativa L.) Mapan P-05 Variety with its Ratoon - Murad, Dini Rahmania Septyani; Sudarmawan, AA; Sudantha, I Made (Journal of Science and Science Education, 2024)
Thisstudy aims to analyze the level of relationship between F1 Mapan P-05 rice plants and their ratoons based on quantitative characteristics. The Mapan P-05 rice variety that was tested was analyzed together with its queen using the kinship analysis method to understand the level of stability of the quantitative traits observed. The use of kinship analysis allows evaluating the genetic relationship between the Mapan P-05 variety and its queen, as well as evaluating the level of stability of the observed quantitative traits. The results showed that through kinship analysis, it was possible to understand the level of genetic relationship between the Mapan P-05 rice variety and its queen, as well as the stability of the observed quantitative traits. This research provides a deeper understanding of the genetic characteristics and stability of quantitative traits in the Mapan P-05 rice variety and its queen, which has important implications in the development and breeding of rice plants to support plant resilience and productivity